ANALISA DAMPAK PROMOSI BELOW THE LINE TERHADAP KEPUTUSAN PEMBELIAN SEKTOR ELEKTRIKAL - Tutut Ratna Wana Setya Ningsih; Arie Mulyati; Lingga Yuliana (Jurnal Bina Bangsa Ekonomika, 2023)
This study aims to analyze the influence of promotion on the purchase decision of electrical products carried out below the line. The study used quantitative descriptive methods, sampling techniques with purposive sampling. Respondents in this study were users of the Philips lamp brand. The data used is primary data. Primary data comes from the distribution of questionnaires through google forms with a total of 125 respondents who are users of the Philips lamp brand spread across Jabodetabek with an age range of 17-55 years. Data analysis techniques using Partial Least Square (PLS). The Likert scale is used in data retrieval with a range of 1-4. The results showed that there was an influence between promotions on purchasing decisions. According to respondents, the Below The Line promotion carried out by the Philips Lighting Brand had a significant impact on making a purchase. With product displays and demonstrations, exhibitions, discounts, coupons and sales promotions, respondents immediately make purchases right away even if they are not planned